The Short Form Score for the Assessment and Quantification of Chronic Rheumatic Affections of the Hands in Daily Clinical Routines—Its Sensitivity to Change and Preliminary Patient Relevant Variation Values: A Pilot Study - Stummer, Ulrike; Rintelen, Bernhard; Leeb, Burkhard F. (Frontiers in Medicine, 2017)
Abstract Objective: The SF-SACRAH was developed to assess hand involvement in rheumatoid arthritis (RA) and hand osteoarthritis (HOA) patients in daily clinical routine. In this pilot study its sensitivity to change should be assessed longitudinally, and preliminary thresholds for patient relevant changes should be figured out. Methods: Ninety-nine out patients suffering from HOA (n = 55) or RA (n = 44) completed the SF-SACRAH once and after approximately 3 months and patients rated their satisfaction (PATSAT) with the disease state (1 = very good to 5 = unsatisfactory) simultaneously. For assessing its sensibility to change, SF-SACRAH changes in patients stable, improving or worsening according to PATSAT were calculated in HOA as well as in RA patients. The respective medians, but also the highest values were taken to estimate patient relevant variation values. SF-SACRAH changes and PATSAT changes to the better or worse in HOA as well as RA patients were analyzed applying the Kruskal Wallis test., In RA patients the DAS28 was additionally calculated. For correlation of SF-SACRAH changes to the EULAR response criteria, Spearman’s rho was calculated. Results: In HOA as well as in RA patients a highly statistically correlation between PATSAT-changes and SF-SACRAH values could be revealed (p < 0.0001 in HOA and p < 0.01 in RA patients respectively). The median changes in SF-SACRAH in patients improving, stable or worsening according to PATSAT were: HOA-patients: PATSAT improving: ΔSF-SACRAH -1.6, PATSAT stable: ΔSF-SACRAH +0.8, PATSAT worsening: ΔSF-SACRAH +1.0; RA-patients: PATSAT improving: ΔSF-SACRAH -0.9, PatSAT stable: ΔSF-SACRAH +0.2, PATSAT worsening: ΔSF-SACRAH +0.8. In RA patients, there is a moderate but significant correlation between DAS28 EULAR response criteria and SF-SACRAH changes (ΔDAS28 improving >0.6: ΔSF-SACRAH -0.4, ΔDAS28 < 0.6: ΔSF-SACRAH +0.0, ΔDAS28 worsening > 0.6: ΔSF-SACRAH +0.5). Correlation of SF-SACRAH changes according to the EULAR response criteria was moderate. Conclusion: The SF-SACRAH constitutes a reliable tool for hand impairment assessment in chronic rheumatic diseases and proved to be sensitive to change in this short term evaluation in HOA as well as in RA patients. Additionally, preliminary patient variation values for improvement (-1.60) and worsening (+1.0) could be figured out.